Drying Characteristics and Product Quality of Lemon Slices Dried with Hot Air Circulation Oven and Hybrid Heatpump Dryers - Yong Hong Lee; Siew Kian Chin; Boon Kuan Chung (International Journal of Science and Engineering, 2015)
In this research, drying characteristics and product quality of Coulomb-force-assisted heatpump and oven dried lemon slices were studied. Lemon slices with 3 mm thickness each, were dried using oven and Coulomb-force-assisted-heatpump dryer with and without auxiliary heater at different drying conditions. It was found that the drying rate of the lemon slices dried by all drying methods showed only falling rate states, which indicates the drying kinetics were controlled by internal moisture diffusion. Oven drying of lemon slices at 60°C showed the highest drying rate among all, followed by oven dried slices at 50°C, Coulomb-force-heater-assisted-heatpump (CF-HT-HP) dried slices at 31°C, Coulomb-force-assisted-heatpump (CF-HP) dried slices at 22°C, oven dried slices at 40°C and heatpump dried slices at 22°C. The average effective moisture diffusivity value for the slices dried with these drying methods was found in the range of 16.2 to 63.8´10-4 mm2min-1. In terms of quality assessment, CF-HP dried lemon slices retained the highest amount of Vitamin C as compared to the lemon slices dried by other drying methods. However, it retained relatively lower amount of total phenolic content (TPC) as compared to oven dried products. Among of all, CF-HP drying method produced dried lemon slices with the highest Vitamin C (6.74 mg AA / g dry weight) whereas oven dried lemon slices at 50°C preserved most of the TPC in the dried slices, which recorded as 13.76 mg GA / g dry weight.